1991
DOI: 10.1079/bjn19910017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of concentration of tannin-rich bean hulls (Vicia fabaL.) on activities of lipase (EC3.1.1.3) and α-amylase (EC3.2.1.1) in digesta and pancreas and on the digestion of lipid and starch by young chicks

Abstract: The effect of different concentrations of tannin-rich field-bean (Viciafaba L.) hulls at 0,20,50, 150 and 300 g/kg dietary inclusion on the activities of lipase (EC 3 . 1 . 1 .3) and a-amylase (EC 3.2.1.1) in digesta and pancreas and on the digestion of lipid and starch was studied in 2-3-week-old male broiler chicks. Low dietary concentrations of tannins (20 and 50 g hulls/kg) enhanced the activity of lipase in digesta from both the jejunum and ileum, the 20 g hulls/kg effecting the greatest enhancement, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 23 publications
1
39
1
2
Order By: Relevance
“…Previous research has demonstrated that a high content of FB tannins in chicken diets decreases the activities of endogenous enzymes in the digestive tract (Longstaff and McNab, 1991), including maltase and sucrase (Iji et al, 2004;Nyamambi et al, 2007). In our study, sucrase activity decreased in turkeys fed diets with the highest content of HT and LT FB seeds, whereas maltase activity decreased in birds fed diets with HT and the highest content of LT seeds.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Previous research has demonstrated that a high content of FB tannins in chicken diets decreases the activities of endogenous enzymes in the digestive tract (Longstaff and McNab, 1991), including maltase and sucrase (Iji et al, 2004;Nyamambi et al, 2007). In our study, sucrase activity decreased in turkeys fed diets with the highest content of HT and LT FB seeds, whereas maltase activity decreased in birds fed diets with HT and the highest content of LT seeds.…”
Section: Discussionmentioning
confidence: 38%
“…An earlier study of HT and LT FB seeds added to rat diets (Zduńczyk et al, 2003) revealed no significant differences in the activities of α-glucosidase, β-glucosidase, α-galactosidase and β-galactosidase, but LT seeds significantly increased the activity of microbial β-glucuronidase. Longstaff and McNab (1991) also observed different effect of dietary tannin levels on enzyme activities in chicken gut microbiota. The cited authors found that diets with low tannin content may stimulate the activities of selected digestive enzymes, whereas diets with high tannin content can inhibit their activities.…”
Section: Discussionmentioning
confidence: 86%
“…Griffiths and Moseley (1980) reported an increased activity of lipase in the digesta when rats were fed on diets containing lOOg tannin-rich field bean hulls/kg. Longstaff and McNab (1991b) also observed an enhanced activity of lipase in the digesta both from jejunun and ileum of young male chicks fed on dietary concentrations of tannins but no stimulatory effect was observed on the activity of digesta amylase. In the present study, it appeared that tannic acid at the above concentrations have stimulatory effect on the activities of these three enzymes.…”
Section: Resultsmentioning
confidence: 80%
“…This deleterious effect is likely due to the reduction in the activities of trypsin and amylase in the digestive tract (Griffiths andMoseley, 1980;Horigome et al , 1988;Longstaff and McNab, 1991b). However, Griffiths and Moseley (1980) and Horigome et al (1988) observed that the activity of lipase increased in the digesta from the rats fed on a diet containing tannin-rich field bean hulls.…”
Section: Concentration the Evidence Gathmvd Fmm This Study Revealedmentioning
confidence: 94%
“…Considering tannin level given for coffee pulp, amount of coffee pulp used in our experiment could be sufficient to induce such inhibition. Moreover, inhibition of amylase and lipase by tannin were also described (Longstaff and Mc Nab, 1991;Quesada et al, 1996;Tamir and Alumot, 1969). This could also explain the observed poor utilisation of feed as a whole.…”
Section: Discussionmentioning
confidence: 84%